1985
DOI: 10.1289/ehp.8564288
|View full text |Cite
|
Sign up to set email alerts
|

Free radicals of benzo(a)pyrene and derivatives.

Abstract: The evidence for biological involvement, the spectroscopic properties (especially EPR), and the reactions, of free radicals derived from benzo(a)pyrene and its methylated, hydroxylated, and fluorinated derivatives are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…DEPs and their extracts both seem to trigger signal transduction pathways involving ROS because the secretion of GM-CSF is strongly decreased after treatment with NAC. Indeed, polycyclic aromatic hydrocarbons such as benzo-[a]pyrene and 1-nitropyrene (23,35) as well as the activation of cytochrome P-450 have been shown to induce the production of ROS. We have shown that the increase in GM-CSF after DEP treatment is inhibited by the radical scavengers NAC, DMTU, and PDTC.…”
Section: Discussionmentioning
confidence: 99%
“…DEPs and their extracts both seem to trigger signal transduction pathways involving ROS because the secretion of GM-CSF is strongly decreased after treatment with NAC. Indeed, polycyclic aromatic hydrocarbons such as benzo-[a]pyrene and 1-nitropyrene (23,35) as well as the activation of cytochrome P-450 have been shown to induce the production of ROS. We have shown that the increase in GM-CSF after DEP treatment is inhibited by the radical scavengers NAC, DMTU, and PDTC.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic metabolites are also formed by direct hydroxylation at position C‐3 and C‐6 []. 6‐OH‐BaP undergoes one‐electron oxidation in the presence of peroxidases or cytochrome P450 to the toxic radical cation 6‐oxy‐BaP that is further oxidized to 1,6‐, 3,6‐, or 6,12‐quinones via hydroquinone and semiquinone radicals []. Quinones themselves are not mutagenic, but the reactive oxygen species generated by these intermediates are responsible for cytotoxic effects [].…”
Section: Metabolism and Molecular Toxicity Of Bapmentioning
confidence: 99%
“…This may be explained by known properties of the chemicals. nC60 is an exceptional free radical scavenger [103,104], while B[a]P has been shown to produce free radicals under a variety of conditions [105]. reported on a loss in mitochondrial membrane potential in a mouse in vitro model, in association with increase in cellular ROS suggesting mitochondria associated apoptosis [107].…”
Section: Protein Expression Profilesmentioning
confidence: 99%